Socioeconomic and geographic variations in antenatal care coverage in Angola: further analysis of the 2015 demographic and health survey - Gebretsadik Shibre; Betregiorgis Zegeye; Dina Idriss-Wheeler; Bright Opoku Ahinkorah; Olanrewaju Oladimeji; Sanni Yaya (BMC, 2020)
Abstract Background In African countries, including Angola, antenatal care (ANC) coverage is suboptimal and maternal mortality is still high due to pregnancy and childbirth-related complications. There is evidence of disparities in the uptake of ANC services, however, little is known about both the socio-economic and geographic-based disparity in the use of ANC services in Angola. The aim of this study was to assess the extent of socio-economic, urban-rural and subnational inequality in ANC coverage in Angola. Methods We analyzed data from the 2015 Angola Demographic and Health Survey (ADHS) using the World Health Organization (WHO) Health Equity Assessment Toolkit (HEAT) software. The analysis consisted of disaggregated ANC coverage rates using four equity stratifiers (economic status, education, residence, and region) and four summary measures (Difference, Population Attributable Risk, Ratio and Population Attributable Fraction). To measure statistical significance, an uncertainty interval (UI) of 95% was constructed around point estimates. Results The study showed both absolute and relative inequalities in coverage of ANC services in Angola. More specifically, inequality favored women who were rich (D = 54.2, 95% UI; 49.59, 58.70, PAF = 43.5, 95% UI; 40.12, 46.92), educated (PAR = 19.9, 95% UI; 18.14, 21.64, R = 2.14, 95% UI; 1.96, 2.32), living in regions such as Luanda (D = 51.7, 95% UI; 43.56, 59.85, R = 2.64, 95% UI; 2.01, 3.26) and residing in urban dwellings (PAF = 20, 95% UI; 17.70, 22.38, PAR = 12.3, 95% UI; 10.88, 13.75). Conclusion The uptake of ANC services were lower among poor, uneducated, and rural residents as well as women from the Cuanza Sul region. Government policy makers must consider vulnerable subpopulations when designing needed interventions to improve ANC coverage in Angola to achieve the 2030 Sustainable Development Goal of reducing global maternal mortality ratio to 70 deaths per 100,000 live births.